Significance of a Positive Toxoplasma Immunoglobulin M Test Result in the United States - Dhakal, Reshika (J Clin Microbiol, 2015)
A positive Toxoplasma immunoglobulin M (IgM) result is often interpreted as a marker of an acute infection. However, IgM can persist for several years, and Toxoplasma commercial IgM diagnostic test kits can yield a number of false-positive results. For these reasons, a chronic Toxoplasma infection can be erroneously classified as an acute infection, resulting in serious adverse consequences, especially in pregnant women, leading to emotional distress and unnecessary interventions, including termination of pregnancy. Interpretation of Toxoplasma serology at a reference laboratory can help differentiate a recently acquired infection from a chronic infection. Serological test results for 451 patients with positive Toxoplasma IgM and IgG test results obtained at nonreference laboratories (NRLs) that were referred to Palo Alto Medical Foundation Toxoplasma Serology Laboratory (PAMF-TSL) to determine whether the patient was acutely or chronically infected were retrospectively reviewed. PAMF-TSL results established that of the 451 patients, 335 (74%) had a chronic infection, 100 (22%) had an acute infection, and 7 (2%) were not infected, and for 9 (2%), results were indeterminate. Positive Toxoplasma IgM and IgG test results obtained at NRLs cannot accurately distinguish between acute and chronic infections. To do so, testing at reference laboratories is required, as mandated in 1997 in a letter from the Food and Drug Administration (FDA) to clinicians and laboratories in the United States.